The life trajectory of the Finnish religious educator - Kuusisto, S; Gearon, L (Taylor and Francis, 2016)
Religious education in Finland is currently adapting to new national religious and secular pluralities. In this pedagogically and socio-politically contested space, a distinctive Finnish approach to religious education is emerging which, the authors argue, reflects tensions between old and new diversities (Vertovec) in a rapidly changing Finnish society. Mindful of this complexity, and the importance of professional religious educators in determining curricula change and societal transformation, the authors use a qualitative life history methodology to assess how Finnish religious professionals view and manage such changes in the light of their own life trajectories.